THE PROBLEMS OF INCREASING THE COMMERCIAL BANK PROFITABILITY - Yakymova, A. M.; Nepyivoda, I. V. (Science and Transport Progress, 2009)
The problems of increase of profitability connected with a financial crisis are considered in the article. Also there are offered the ways of increase of profitability of commercial banks.